Jamun for health and wealth - Singh, Sanjay; Singh, A K; Mishra, D S; Rao, V V Appa; Saroj, P L (Indian Horticulture, 2019)
In recent years, jamun fruit is becoming popular among people due to its rich medicinal values, particularly for its anti-diabetic properties and antioxidant phytonutrients. It is one of the very important fruits and needs attention on scientific cultivation in different parts of the country. Looking at the importance of this fruit, the demand for its planting material is increasing. Soft wood grafting in March-April and patch budding in March may be followed for multiplication of elite jamun plants.